If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 62 = 6x + 10 Reorder the terms: 62 = 10 + 6x Solving 62 = 10 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 62 + -6x = 10 + 6x + -6x Combine like terms: 6x + -6x = 0 62 + -6x = 10 + 0 62 + -6x = 10 Add '-62' to each side of the equation. 62 + -62 + -6x = 10 + -62 Combine like terms: 62 + -62 = 0 0 + -6x = 10 + -62 -6x = 10 + -62 Combine like terms: 10 + -62 = -52 -6x = -52 Divide each side by '-6'. x = 8.666666667 Simplifying x = 8.666666667
| 100+12h=23 | | .90x+2.50=18.50 | | 20m=10 | | y=-6*0 | | p^2-4=-2p | | a-.04a=384 | | y=-6*7 | | 2x+8=2+4x | | y=-6*8 | | 11c-c=95 | | y=-6*3 | | 2(4+3)= | | 6x-2=7-2x | | 33/7-45/6 | | y=-6*1 | | 7.5+x=4.5+4c | | 3/4x-3=9 | | 45=18a-45 | | 3+(7-2)= | | (4x+3)/9-(2x+1)/2 | | r=ut | | 45/6-33/7 | | y=8+9 | | y=-4+9 | | 6x+11=53 | | y=-1+9 | | 2/5n=8 | | y=-5+9 | | y=0+9 | | 2x^3+7=-47 | | p+.12p=560 | | 2-4(0.111x)=-6 |